Phenotypic Changes in T Cell and Macrophage Subtypes in Perivascular Adipose Tissues Precede High-Fat Diet-Induced Hypertension - Kumar, Ramya Kalyana; Yang, Yongliang; Contreras, Andres G.; Garver, Hannah; Bhattacharya, Sudin; Fink, Gregory D.; Rockwell, Cheryl E.; Watts, Stephanie W. (Frontiers in Physiology, 2021)
Perivascular adipose tissue (PVAT) may connect adiposity to hypertension because of its vasoactive functions and proximity to blood vessels. We hypothesized that immune cell changes in PVATs precede the development of HFD-induced hypertension. Both sexes of Dahl S rat become equally hypertensive when fed a high fat diet (HFD). Further, both sexes would have similar immune cell composition in PVATs with the development and progression of hypertension. Male and female Dahl S rats were fed a regular (10% calories from fat; CD) diet or a HFD (60%) from weaning. PVATs from around the thoracic aorta (APVAT) and small mesenteric vessels (MRPVAT) were harvested at 10 weeks (pre-hypertensive), 17 weeks (onset) or 24 (hypertensive) weeks on diet. RNA-sequencing in MRPVAT at 24 weeks indicated sex-differences with HFD (> CD) and diet-differences in males (> females). The top 2 out of 7 immune processes with the maximum number of differentially expressed genes were associated with immune effector processes and leukocyte activation. Macrophages and T cells (and their activation status), neutrophils, mast, B and NK cells were measured by flow cytometry. Sex-specific changes in the number of CD4 memory T cells (males > females) and M2-like macrophages (females > males) in PVATs occur with a HFD before hypertension developed. Sex-differences became more prominent with the development and progression of hypertension, driven by the diet (HFD > CD). These findings suggest that though the magnitudes of increased blood pressure were equivalent in both sexes, the associated phenotypic changes in the immune subsets within the PVATs were different in the male vs the female with the development and progression of hypertension.